Alteplase in COVID-19 severe hypoxemic respiratory failure: the TRISTARDS multicenter randomized trial - Landoni, Giovanni; Chowdary, Pratima; Meziani, Ferhat; Creteur, Jacques; De Schryver, Nicolas; Motsch, Johann; Henrichmoeller, Ingrid; Pagès, Alain; Peter, Nuala; Danays, Thierry; Weigand, Markus A. (Annals of intensive care, 2024)
Pulmonary intravascular thrombus formation has been widely observed in patients with respiratory failure, for example, in patients with SARS-CoV-2 infection (COVID-19). The aim of this study was to evaluate the efficacy/safety of alteplase thrombolysis in COVID-19 severe hypoxemic respiratory failure. In this multicenter, open-label study, patients were randomized to receive alteplase (low- or high-dose) over 5 days plus standard of care (SOC), or SOC alone. The primary endpoint was time to clinical improvement (≥ 2-point decrease on WHO Clinical Progression Scale, or hospital discharge) up to Day 28. Secondary endpoints included all-cause mortality at Day 28, treatment failure at Day 28 and change in arterial oxygen partial pressure/fractional inspired oxygen (PaO2/FiO2) ratio at Day 6 versus baseline.